Psikoedukasi Dampak Body Shaming pada Remaja - Sumi Lestari (Jurnal Pengabdian Pada Masyarakat, 2020)
PSYCHOEDUCATION OF THE IMPACT OF BODY SHAMING ON ADOLESCENT. Body shaming is a form of commenting on or embarrassing the physical condition of others. The rise of the phenomenon of body shaming in society occurs because individuals are considered not in accordance with the ideal standard of perfection of appearance that applies in society so that the community is considered as a social controller of perfection of appearance. In addition, social comparison and physical attractiveness of individuals play an important role in evaluating and evaluating the appearance of individual bodies. Body shaming often occurs in children, adolescents and adults, this happens because it is considered a normal and normal behavior, other than that the perpetrator does not understand the impact of his body shaming. The impact of body shaming on victims, namely, psychological impacts include; anxiety, fear, worry, insecurity, low self-esteem, eating disorders, insomnia, stress, and the tendency for body dysmorphic disorders, while the behavioral effects include withdrawing from the social environment, being alone, unhealthy diets, excessive care and exercise. Preventive efforts undertaken by the government to reduce body shaming behavior in the community are by making ITE Law Article 27 paragraph 3 and Article 45 paragraph 1 and if verbal body shaming is directly addressed to someone, it will be subject to articles 310 and 311 of the Criminal Code with the threat of punishment 9 prison month.